2023
DOI: 10.1038/s41598-023-29855-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multicenter trial to assess posterior capsule opacification and glistenings in two hydrophobic acrylic intraocular lenses

Abstract: To evaluate the long-term posterior capsule opacification (PCO) formation, and glistening rate of the HOYA Vivinex (XY1) IOL compared to Alcon AcrySof (SN60WF). In this prospective, multicentric, randomized, paired-eye, open-label study, we included 87 subjects that underwent cataract surgery with IOL implantation, with 67 patients completing the 3-year follow-up. The completer population consisted of 32 subjects implanted with XY1 and 35 implanted with SN60WF. Primary endpoints consisted of the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Other issues have also been observed, such as the loss of pseudoaccommodative properties after 2 years and a high post-cataract rate of 100 % after 1 year with the 1CU design. In this context, a recent publication by Auffarth et al is noteworthy [8]. They demonstrated that Hoya Vivinex IOLs, specifically the XY1 design, exhibited significantly less glistening over 3 years compared to Alcon AcrySof SN60WF (Alcon, Fort Worth, TX, USA), and the rate of after-cataract was remarkably low [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other issues have also been observed, such as the loss of pseudoaccommodative properties after 2 years and a high post-cataract rate of 100 % after 1 year with the 1CU design. In this context, a recent publication by Auffarth et al is noteworthy [8]. They demonstrated that Hoya Vivinex IOLs, specifically the XY1 design, exhibited significantly less glistening over 3 years compared to Alcon AcrySof SN60WF (Alcon, Fort Worth, TX, USA), and the rate of after-cataract was remarkably low [8].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recent publication by Auffarth et al is noteworthy [8]. They demonstrated that Hoya Vivinex IOLs, specifically the XY1 design, exhibited significantly less glistening over 3 years compared to Alcon AcrySof SN60WF (Alcon, Fort Worth, TX, USA), and the rate of after-cataract was remarkably low [8].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent studies with 3 years of follow-up found no glistenings in Clareon IOLs and none to only a few in Vivinex IOLs. 31,32 The prediction error of eyes implanted with an XY1 IOL was, on average, slightly myopic, whereas that of eyes implanted with a CNA0T0 IOL was slightly hyperopic (À0.26 D vs 0.17 D). In this study, we used the lens constants as suggested by the manufacturer at the start of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent studies with 3 years of follow-up found no glistenings in Clareon IOLs and none to only a few in Vivinex IOLs. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Overall lens diameter is 13.0 mm with a 6.0 mm optic zone. A proprietary posterior surface treatment increases lens/capsule adhesion to reduce the potential for PCO 11 and the textured edges of the optic reduce the likelihood of dysphotopsia. The base refractive power of the 6.0 mm optic provides distance vision, while intermediate and near vision are provided by the 3.2 mm central diffractive zone on the anterior surface.…”
Section: Introductionmentioning
confidence: 99%